Socialização e comprometimento organizacional em uma instituição federal de ensino - Arraes, Lia Fontenele (2018)
The aim of the present study is to analyze the influence of the initial process of organizational socialization on the organizational commitment of administrative technicians in a public institution of education. As a theoretical basis, this work presents the socialization factors of Borges et al. (2010) and the three-dimensional approach of the commitment of Bastos et al. (2011). The research can be classified by descriptive character, carried out by means of a survey, adopting a cross-section. The study population comprises Administrative Technicians in probationary stage. Data were collected through questionnaires, which collected sociodemographic data and included the Organizational Socialization Inventory (Borges et al., 2010) and the Organizational Engagement Scale (Bastos et al., 2011). For the analysis of the data obtained with the questionnaires, SPSS statistical software was used in its version 20. Factorial analyzes were performed to determine the factor scores of the scales and Pearson correlation to determine the relationship strength of the variables. Six factors of organizational socialization were found: domain of procedures and activities, integration with people, alignment with organizational objectives, proactivity, competence and language and three dimensions of organizational commitment: affective, normative and instrumental. The factors in line with organizational objectives, integration with people, competence, proactivity and mastery of procedures and activities positively influence the affective commitment. The language factor negatively influences the normative commitment. The domain factor of the procedures and activities negatively influences the instrumental commitment. In the face of the findings, the organization must make every effort to ensure that the administrative technical staff know and are in tune with the organizational goals and feel accepted and integrated in their work team and thus increase the emotional affection, identification and involvement of the employee with the organization.